The importance of Prophylaxis for Pulmonary Thromboembolism in postoperative orthopedic surgeries (Research, Society and Development, 2024)
Introduction: Pulmonary thromboembolism (PE) occurs when an embolus obstructs the pulmonary artery or its branches, reducing blood flow to the lung. Thromboprophylaxis can be mechanical or pharmacological. Fractures and arthroplasties of the hip and knee have a higher risk of thromboembolism. Objective: The present study aimed to evaluate the importance of PE prophylaxis in the postoperative period of orthopedic surgeries, contributing to the construction of knowledge based on the literature. Materials and Methods: This is an integrative literature review on the importance of pulmonary thromboembolism prophylaxis in the postoperative period of orthopedic surgeries. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Pulmonary Thromboembolism”; “Prophylaxis”; “Orthopedic Surgeries”, in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (BVS) databases. Results and Discussion: Thrombosis is explained by Virchow's triad. In orthopedic procedures such as total knee arthroplasty, total hip arthroplasty and hip fracture surgery, the risk of venous thromboembolism (VTE) is high. It is common to use LMWH and DOACs. However, it is necessary to individualize each case, especially when it comes to high-risk patients. Conclusion: Many studies focus on the prophylaxis of VTE and PE. Rivaroxaban is highly recommended, and evidence suggests that ASA may be more effective and safer than warfarin and LMWH in certain cases. Adopting a combined approach to prevention reduces the overall risk of thromboembolic complications.